The Progranulin Cleavage Products, Granulins, Exacerbate TDP-43 Toxicity and Increase TDP-43 Levels - Salazar, D. A.; Butler, V. J.; Argouarch, A. R.; Hsu, T.-Y.; Mason, A.; Nakamura, A.; McCurdy, H.; Cox, D.; Ng, R.; Pan, G.; Seeley, W. W.; Miller, B. L.; et al. (The Journal of neuroscience, 2015)
Mutations in the human progranulin gene resulting in protein haploinsufficiency cause frontotemporal lobar degeneration with TDP-43 inclusions. Although progress has been made in understanding the normal functions of progranulin and TDP-43, the molecular interactions between these proteins remain unclear. Progranulin is proteolytically processed into granulins, but the role of granulins in the pathogenesis of neurodegenerative disease is unknown. We used a Caenorhabditis elegans model of neuronal TDP-43 proteinopathy to specifically interrogate the contribution of granulins to the neurodegenerative process. Complete loss of the progranulin gene did not worsen TDP-43 toxicity, whereas progranulin heterozygosity did. Interestingly, expression of individual granulins alone had little effect on behavior. In contrast, when granulins were coexpressed with TDP-43, they exacerbated its toxicity in a variety of behaviors including motor coordination. These same granulins increased TDP-43 levels via a post-translational mechanism. We further found that in human neurodegenerative disease subjects, granulin fragments accumulated specifically in diseased regions of brain. To our knowledge, this is the first demonstration of a toxic role for granulin fragments in a neurodegenerative disease model. These studies suggest that presence of cleaved granulins, rather than or in addition to loss of full-length progranulin, may contribute to disease in TDP-43 proteinopathies.